Duadic codes over F2 + uF2 - Ling, San (2013)
Duadic codes over F2+uF2 are introduced as abelian codes by their zeros. This is the function field analogue of duadic codes over Z4 introduced recently by Langevin and Solé. They produce binary self-dual codes via a suitable Gray map. Their binary images are themselves abelian, thus generalizing a result of van Lint for cyclic binary codes of even length. We classify them in modest lengths and exhibit interesting non-cyclic examples.